2018
DOI: 10.1002/bjs5.80
|View full text |Cite
|
Sign up to set email alerts
|

Major trauma in older persons

Abstract: BackgroundGlobally, populations are ageing, creating challenges for trauma system design. Despite this, little is known about causes of injury and long‐term outcomes in older injured patients. This study aims to describe temporal trends in the incidence, causes and functional outcomes of major trauma in older adults.MethodsThe population‐based Victorian State Trauma Registry was used to identify patients with major trauma aged 65 years and older with a date of injury between 1 January 2007 and 31 December 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 28 publications
6
68
0
4
Order By: Relevance
“…This study compared the characteristics of major trauma in younger and older patients. Consistent with previous studies of major trauma in older adults, we found that falls from standing were the most common mechanism of injury and as age increased the proportion of falls increased . Similar to a study undertaken in Victoria, we found that with each increasing age group the proportion of patients who received definitive care at a non‐major TC increased .…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This study compared the characteristics of major trauma in younger and older patients. Consistent with previous studies of major trauma in older adults, we found that falls from standing were the most common mechanism of injury and as age increased the proportion of falls increased . Similar to a study undertaken in Victoria, we found that with each increasing age group the proportion of patients who received definitive care at a non‐major TC increased .…”
Section: Discussionsupporting
confidence: 89%
“…The primary outcome was transport to the TC and the secondary outcome, in‐hospital mortality. We defined older persons as those aged ≥65 years, which is also in accordance with previous definitions of older persons in trauma studies …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations